Focalisation averbale vs focalisation verbale en français parlé - Noalig Tanguy (Discours)
The aim of this paper is to compare two types of (syntactic) structures which are frequently used in spoken French. While they are both uttered in two parts, one structure contains a verb and the other is based on a verbless element:[a] à la caisse ils se pèsent [Sabio, 1995 : 114] = at the checkout, they are weighed[b] très bien ta vie [CTFP : 32] = very pleasant, your lifeWe will show that such examples follow the same prosodic pattern. Construction [a] and [b] are uttered with a pause which splits them into two intonation groups. The first conveys a modal intonation which makes it autonomous while the second sounds like an appendix or extension. Furthermore, the same pragmatic effect is obtained by both structures, as they result from the same focalisation process, entailing the fronting of a rhematic element.We will hence suggest an identical interpretation for such structures, as they can be analysed as a 'nucleus' + a 'suffix'. We will finally show that these two examples can be analysed as contextual variants for the same process, and that these variants are the result of a constraint created both by the type of verb and by the syntactic type of the subject which underlie the construction.